2012
DOI: 10.1016/j.otsr.2011.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Total ankle arthroplasty and coronal plane deformities

Abstract: Level IV. Retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…8,9,[19][20][21][22][23][24][25][26] One cannot isolate many studies reporting on outcomes of TARs combined with osteotomies, as these procedures are part of the whole spectrum of surgery performed for ankles with greater than 10 coronal plane deformity. Doets and colleagues 20 reported on his series of 15 TARs in varus ankles, requiring a medial malleolar lengthening osteotomy.…”
Section: Clinical Results In the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…8,9,[19][20][21][22][23][24][25][26] One cannot isolate many studies reporting on outcomes of TARs combined with osteotomies, as these procedures are part of the whole spectrum of surgery performed for ankles with greater than 10 coronal plane deformity. Doets and colleagues 20 reported on his series of 15 TARs in varus ankles, requiring a medial malleolar lengthening osteotomy.…”
Section: Clinical Results In the Literaturementioning
confidence: 99%
“…A French study 25 reviewed the outcomes in 21 TARs with deformity of greater than 10 , all requiring additional procedures, many of which were osteotomies. Six (28%) of 21 ankles had residual postoperative deformity requiring further corrective surgery (osteotomies), whereas 3 TARs (14%) had already failed (requiring revision or fusion) at 3 years.…”
Section: Clinical Results In the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is considered essential to establish a neutrally aligned ankle after TAA for successful long-term outcomes and to prevent complications (4,11,21). Recently, several studies have shown that satisfactory outcomes can be obtained following TAA even in ankles with substantial preoperative coronal deformity (4,(9)(10)(11)(12). The key to achieving postoperative neutral alignment seems to be associated with additional procedures at the time of TAA.…”
Section: Discussionmentioning
confidence: 99%
“…However, experts are yet to arrive at a consensus on whether preoperative coronal deformity is associated with postoperative poor outcomes. Some authors reported that preoperative coronal malalignment was associated with poor outcomes (7,8) and others reported no association between preoperative coronal varus deformity and postoperative clinical outcomes (2,(9)(10)(11)(12). As a limitation, most previous studies performed simultaneous osteotomy at the time of TAA for ankles with severe varus coronal deformity.…”
Section: Introductionmentioning
confidence: 99%